The study on the influence of the Master Chin Kung Model towards the spread and the growth of the Amitabha Buddhist Society Malaysia = Kajian pengaruh model Master Chin Kung terhadap penyebaran dan perkembangan Persatuan Penganut Agama Buddha Amitabha Malaysia - Poey, Tiang Peow (2015)
This thesis is a study on the influence of the Master Chin Kung Model towards the spread and the growth of Amitabha Buddhist Society Malaysia (PPABAM) which has been located in Malaysia. The survey on the influence of the Master Chin Kung Model towards the administration and management of the various activities carried out by PPABAM is comprised of four aspects namely education, culture, welfare, and cultivation, and they serve as the focus of this study in which it facilitates our understanding in regards to the PPABAM’s dissemination and development trend that plays a vital role in spreading the religious teachings of Buddhism in Malaysia. The Master Chin Kung Model's Four Holy Aims comprises of: 1. Restoring Buddhism through traditional Buddhism education, which focuses on the worldly teachings, the universe, and the hereafter as taught through the teachings of Dharma Buddha by the founder of Buddhism which is Buddha Shakyamuni. 2. To encourage and develop the use of Classical Chinese language widely. Proficiencies in Classical Chinese Language may allow a person to gain more comprehensive knowledge and a deeper understanding as recorded in Si Ku QuanShu《四库全书》 and Qianlong Dazangjing《乾隆大藏经》. 3. To encourage and expand the concept and the spirit of family ties set out in the cultural tradition of the Chinese. The concept and spirit of family ties are recorded in the holy book of Dizigui; 4. To promote and spread multi-religious and multi-cultural education. This could transform and resolve the deteriorating conflicts often times occurring among people and could also maintain global security. The objective of this thesis is aimed at reviewing the extent on the influence of Master Chin Kung Model towards the spread and development of PPABAM in Malaysia and the main reasons of PPABAM’s application of it; particularly to benefit the believers and the local community in general. The research method of this thesis is to use both qualitative and quantitative methods. Qualitative methods include library research methods, observation and interview sessions; whilst quantitative method is carried out through questionnaire surveys among the devotees of PPABAM. This thesis uses the new Structural Functionalism Theory – the AGIL Model which was founded by sociologist Talcott Parsons, to analyse the collected data. The AGIL Model consists of four main factors, namely A: Adaptation, G: Goal Attainment, I: Integration, and L: Latency. The results of this study will reflect PPABAM information on how to implement and apply the Master Chin Kung Model in the process of dissemination and development of Buddhism in Malaysia and the main reasons of PPABAM in applying it. The researcher of this study argue that the spread and development of PPABAM are aligned to a part of the saga of Master Chin Kung, whom at this stage had devoted his old age in developing the Four Holy Missions. Thus, it influenced the direction and the course of PPABAM in the process of disseminating and developing Buddhism education in general, and the teachings of the Pure Land Amitabha particularly in Malaysia.